Architecture and challenges of system models for marine data transmission networks - Shengming JIANG; Lige GE; Yanli XU (Dianxin kexue)
Marine data transmission networks are different from terrestrials in the following aspects: high dynamics and uncertainties in network boundary, network path and communication and networking resources, heterogeneities of communication media and asymmetric communication performance, complexity of marine communication network resources with limited capabilities and ability, and high complexity and mobility of marine users with low distribution densities etc.In view of the above peculiarities for communication network in the marine space, an SM for marine data transmission network was studied from the aspects of business characteristics, network composition, network characteristics and architecture, and five challenges faced by the architecture were focused on, including adaptability, intelligent networking, transparent transmission, roaming support and secure transmission.